Methods for Estimating Endotracheal Tube Insertion Depth in Neonates: A Systematic Review and Meta-Analysis - Razak, Abdul; Faden, Maher (American Journal of Perinatology, 2020)
Objective To systematically review the methods for estimating endotracheal tube (ETT) insertion depth in neonates.Study Design Medline, Embase, Cochrane Central, and Cumulative Index to Nursing and Allied Health Literature databases searched for randomized clinical trials (RCTs). RCTs comparing two or more different methods to estimate ETT insertion depth were included. Two co-authors independently extracted the data and assessed the risk of bias. The primary outcome includes the proportion of optimally placed ETT tips identified on chest X-ray.Results Eight RCTs evaluating seven different estimation methods were included. Trials varied defining the optimal position of the ETT tip. Overall, the percentage of optimal position ranged from 8.8 to 93%. The weight, gestation nomogram, and vocal cord estimation methods resulted in malpositioning of ETT tips in more than half of infants ≤30 weeks' gestational age. The rates of optimal ETT tip placement with the digital palpation method differ between moderately (83–93%; two RCTs) and extremely (47%; one RCT) preterm infants. Meta-analysis showed no difference between weight-based and digital palpation methods (relative risk = 0.88; 95% confidence interval = 0.75–1.04; three RCTs; participants = 205; I2 = 0%; quality of evidence, low).Conclusion Commonly used estimation methods for ETT tip placement are inaccurate and unreliable. Further research is required to improve the accuracy of estimation methods and also to identify the usefulness of the digital palpation method in large clinical trials.
Keywords: infants; neonates; endotracheal tube; ventilation; ETT